2019
DOI: 10.2196/15130
|View full text |Cite
|
Sign up to set email alerts
|

A Smartphone App Is Feasible for Outpatient Cirrhotic Ascites Management

Abstract: Background Ascites, or accumulation of abdominal free fluid, develops in two-thirds of patients with cirrhosis. Ascites is painful and, if inadequately managed, can lead to life-threatening complications, including spontaneous bacterial peritonitis and kidney failure. Body weight is an effective proxy for ascites volume; therefore, monitoring daily weights is recommended for optimal ascites management. At present, patients with ascites rarely proactively alert providers of significant weight gains,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…14 Bloom et al showed that administering Bluetoothenabled scales to patients with ascites resulted in successful (70%) transmission of weights during the study period. 32 Lastly, in an observational study where tablets for telemonitoring (in-home monitoring of vital signs) were provided to post-liver transplantation patients, high use was associated with lower readmissions. 33 However, giving devices to everyone overlooks key adoption and use factors.…”
Section: Antecedents Of Technology Acceptance and Adoptionmentioning
confidence: 99%
“…14 Bloom et al showed that administering Bluetoothenabled scales to patients with ascites resulted in successful (70%) transmission of weights during the study period. 32 Lastly, in an observational study where tablets for telemonitoring (in-home monitoring of vital signs) were provided to post-liver transplantation patients, high use was associated with lower readmissions. 33 However, giving devices to everyone overlooks key adoption and use factors.…”
Section: Antecedents Of Technology Acceptance and Adoptionmentioning
confidence: 99%